2019
DOI: 10.1530/joe-18-0596
|View full text |Cite
|
Sign up to set email alerts
|

The melanocortin pathway and control of appetite-progress and therapeutic implications

Abstract: The initial discovery thatob/obmice become obese because of a recessive mutation of the leptin gene has been crucial to discover the melanocortin pathway to control appetite. In the melanocortin pathway, the fed state is signaled by abundance of circulating hormones such as leptin and insulin, which bind to receptors expressed at the surface of pro-opiomelanocortin (POMC) neurons to promote processing of POMC to the mature hormone α-melanocyte-stimulating hormone (α-MSH). The α-MSH released by POMC neurons the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 454 publications
(492 reference statements)
2
125
0
8
Order By: Relevance
“…While MC3R neurons likely contribute to behavioral adaptation to fasting and nutrient partitioning, MC4R neurons are involved in feeding behavior, adaptive thermogenesis, and glucose homeostasis (10). Therefore, this system provides a logical target for developing drugs for treating cachexia, obesity, and diabetes (8,(11)(12)(13)(14). The pathophysiological processes of many illnesses increase the melanocortin tone that suppresses appetite and anabolism, leading to anorexia and body weight loss, with inflammation as an essential driver (15).…”
Section: Introductionmentioning
confidence: 99%
“…While MC3R neurons likely contribute to behavioral adaptation to fasting and nutrient partitioning, MC4R neurons are involved in feeding behavior, adaptive thermogenesis, and glucose homeostasis (10). Therefore, this system provides a logical target for developing drugs for treating cachexia, obesity, and diabetes (8,(11)(12)(13)(14). The pathophysiological processes of many illnesses increase the melanocortin tone that suppresses appetite and anabolism, leading to anorexia and body weight loss, with inflammation as an essential driver (15).…”
Section: Introductionmentioning
confidence: 99%
“…Tinaja and Molino cavefish consume more than surface fish in the laboratory and this difference is associated with mutations in melanocortin receptor 4 (MC4R) (Aspiras et al, 2015). MC4R is a G protein-coupled receptor expressed in the hypothalamus that integrates leptin and insulin signals to modulate appetite (Baldini & Phelan, 2019). Human variation at the MC4R locus is associated obesity, anorexia, and one study found a human SNP in MC4R associated with lutein levels in the serum (Borel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…POMC is then processed via prohormone convertase 1 into the αmelanocyte-stimulating hormone (α-MSH), which activates the melanocortin 4 receptor (MC4R). This finally mediates a feeling of satiety, reduces food intake, and enhances energy expenditure [10][11][12]. In summary, the disease-causing variants in the LEPR gene found in the two patients interrupt the leptin-melanocortin signalling pathway and lead to severe early-onset obesity, pronounced hyperphagia, and permanent food-seeking behaviour.…”
Section: Diagnosismentioning
confidence: 99%